The performative presidency crisis and resurrection during the Clinton years - Mast, Jason L. (Cambridge cultural social studies, 2013)
"The Performative Presidency brings together literatures describing presidential leadership strategies, public understandings of citizenship and news production and media technologies between the presidencies of Theodore Roosevelt and Bill Clinton and details how the relations between these spheres have changed over time. Jason Mast demonstrates how interactions between leaders, public and media are organized in a theatrical way and argues that mass mediated plot formation and character development play an increasing role in structuring the political arena. He shows politics as a process of ongoing performances staged by motivated political actors, mediated by critics and interpreted by audiences, in the context of a deeply rooted, widely shared system of collective representations. The interdisciplinary framework of this book brings together a semiotic theory of culture with concepts from the burgeoning field of performance studies"--